Dynamics of the cover and land use of the páramo de paja blanca regional natural park (Nariño, Colombia) - López Bolaños, María Alejandra; Portillo Daza, Angie Nataly; Narváez Bravo, Germán Edmundo (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This study analysed the main changes in land cover and land use that occurred in the area of influence of the Páramo de Paja Blanca Regional Natural Park in the period 2005-2020, which includes a work area of 17,328.4 hectares. , distributed in seven municipalities in the south of Nariño (Colombia): Pupiales, Iles, Gualmatán, Guachucal, Contadero, Ospina and Sapuyes, which are located in the physiographic zone known as Nudo de los Pastos and its area is part of the ecosystems called altoandinos. The coverage classification parameters set out in the Corine Land Cover methodology adapted for Colombia were followed, within the established period (2005-2020), and the legend of agricultural land uses of the Rural Agricultural Planning Unit (UPRA). In the results, a total of 16 coverages were obtained for the year 2020 and 13 units for the year 2005. Regarding land use for this period, there were a total of six uses (residential-commercial, livestock, agricultural, agricultural, forestry and agroforestry). Based on the above, 15 types of change were identified, both for coverage and land use, which allowed establishing nine causes with the factors that caused these changes.